Persepsi Konsumen terhadap Transparansi Biaya Perbankan dan Pengaruhnya terhadap Pengelolaan Risiko Keuangan Bank - Dianningsih; Kristanto, Giovanny Bangun; Istiningrum, Farida (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
This study aims to examine the impact of banking fee transparency on financial risk management in Banyumas Regency. Focusing on five main variables—clarity of fee information, ease of information access, perceived fairness, customer satisfaction, and technological systems—the research involved 116 respondents utilizing digital banking services. A quantitative approach using survey methods was employed to identify causal relationships between independent and dependent variables. The analysis revealed that fee transparency significantly influences consumer trust and loyalty, which, in turn, affects the effectiveness of financial risk management. Ease of information access, customer satisfaction, and technological systems positively and significantly impact financial risk management. Conversely, perceived fairness of fees showed no significant influence. Simultaneously, the five variables collectively contributed significantly to supporting financial risk management. This study highlights the importance of information transparency and technological innovation in creating an inclusive, trustworthy, and sustainable banking system. The findings provide insights for financial institutions to design strategies that strengthen customer relationships and for regulators to develop policies promoting transparency and consumer protection. These efforts are expected to enhance public trust in the banking system and support overall financial stability.